Deadlocks and Turns of Historical Analysis of Early Capitalism: Capitalists in Spite of Themselves by R. Laсhmann - Дмитрий Михайлович Жихаревич; Андрей Владимирович Резаев (Journal of Economic Sociology, 2013)
Detailed description in the text